Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Sociology
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique